2020
DOI: 10.1002/asia.202000583
|View full text |Cite
|
Sign up to set email alerts
|

Grafting Molecular Cobalt‐oxo Cubane Catalyst on Polymeric Carbon Nitride for Efficient Photocatalytic Water Oxidation

Abstract: Supporting information for this article is given via a link at the end of the document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…In Figure 3a, two peaks around 13°and 27°are attributed to the in-plane structural of repeated triazine units (100) and interlayer stacking motif (002) crystal plane, respectively. [23] It is also worth noting that the (002) peak of g-C 3 N 4 is slightly red-shift from 27.5°to 27.64°, revealing the contractive interplanar distance. [24] Besides, compared to bulk CN, the stronger intensity of the (002) peak of the NCN indicates the regularized 2D conjugated structure can be introduced by acid intercalation.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In Figure 3a, two peaks around 13°and 27°are attributed to the in-plane structural of repeated triazine units (100) and interlayer stacking motif (002) crystal plane, respectively. [23] It is also worth noting that the (002) peak of g-C 3 N 4 is slightly red-shift from 27.5°to 27.64°, revealing the contractive interplanar distance. [24] Besides, compared to bulk CN, the stronger intensity of the (002) peak of the NCN indicates the regularized 2D conjugated structure can be introduced by acid intercalation.…”
Section: Resultsmentioning
confidence: 91%
“…The XRD and FT‐IR tests are conducted to reveal the crystal phase and surface chemical groups. In Figure 3a, two peaks around 13 ° and 27° are attributed to the in‐plane structural of repeated triazine units (100) and interlayer stacking motif (002) crystal plane, respectively [23] . It is also worth noting that the (002) peak of g‐C 3 N 4 is slightly red‐shift from 27.5° to 27.64°, revealing the contractive interplanar distance [24] .…”
Section: Resultsmentioning
confidence: 99%
“…The GaP/TiO 2 /Ga 2 O 3 /TiO 2 /Ga 2 Se 3 sample presented a lower overpotential (−0.54 V) than that of GaP/Ga 2 O 3 /Ga 2 Se 3 (−0.58 V). Because the photocatalytic H 2 evolution activity was highly related to the overpotential of tested samples, [ 9,56 ] the GaP/TiO 2 /Ga 2 O 3 /TiO 2 /Ga 2 Se 3 photocatalyst exhibited better activity for H 2 evolution.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, our group have demonstrated an in situ construction strategy to build cobalt‐oxo cubane complex motifs on the pyridine‐functionalized PCN surface (PCNPy–Co III 4 O 4 ). [ 148 ] As shown in Figure a–c, the cobalt‐oxo cubane complex functionalized PCN exhibited much higher photocatalytic activity for water oxidation toward oxygen evolution as compared to other control samples having different ways of cobalt modifications. The electrochemical analyses showed that grafting Co III 4 O 4 units on the surface of PCN can effectively promote the separation of photogenerated charge carriers, thereby improving the photocatalytic OER activity.…”
Section: Strategies Of Pcn Functionalizationsmentioning
confidence: 99%
“…Reproduced with permission. [ 148 ] Copyright 2020, WILEY‐VCH. d) Photocatalytic hydrogen evolution amount versus irradiation time for PCN 0 , PCN 0 :Ni, PCN–O, PCN–NOH, PCNNOH:Ni, and PCN–NOH:Pt catalysts, e) transient photocurrent responses at bias of 0 V, d) proposed structure of oxime–Ni 2+ in PCN and redox cycle of Ni 2+ during the HER, and f) schematic diagram of excitation and reactions on PCN–NOH:Ni sample under light irradiation.…”
Section: Strategies Of Pcn Functionalizationsmentioning
confidence: 99%